Co-metathesis reaction of crude palm oil and ethene - Ahmad, F.B.H.; Hamdan, S.; Yarmo, M.A.; Alimunir, A. (1995)
The co-metathesis reaction of crude palm oil with ethene in the presence of WCL6/Me4Sn, followed by termination of this reaction with methanol, gives terminal alkenes. The major metathesis products are 1-decene and methyl 9-decenoate. © 1995, American Oil Chemists’ Society. All rights reserved.